Physical self-development of female future officers as component physical education at the military academy - V. Sliusarchuk (Kazimierz Wielki University, 2016)
The study examined the state of development of approaches to ensuring the physical self-development of female - future officers during the physical training at the military academy. General scientific methods, in particular, analysis, systematization, synthesis. More than 60 sources of information were processed and selected the most informative in terms of achieving the goal. The reason for the choice the above sources were being a result of the use of search engines and keywords. It has been established that there is still no common view of the categorical apparatus problem being investigated. At the same time, the implementation in the learning process of girls - the future officers of physical self-development is one of the promising ways to increase effectiveness of physical education. The essence of the term «Self-development», then it must be seen as a conscious, purposeful process development of potentials, qualities or the formation of entirely new traits, opportunities based on the intrinsic impulses of the individual and (or) external impacts. Further research is needed to ensure physical self-development of girls - future officers during their training at the military academy.